Type of light in sand fly captures (diptera:psychodidae) (2012)
The number of cases of visceral leishmaniasis in Brazil has been gradually increasing, and one of the strategies to reduce the transmission of this disease is based on the control of the adult forms of its vectors. It is therefore of great epidemiological importance to develop more refined methods for monitoring and controlling its vectors, which are the phlebotomine sand flies, or biting midges. The present study compares the attraction exercised by UV light in comparison with conventional incandescent, or white, light in catching phlebotomine sand flies. Traps baited with UV light caught higher numbers of these flies than traps baited with white light, indicating the potential use of UV light, especially in locations of low demographic density of the flies.